Chaos control via Mathieu-Van der Pol system and Linear Optimal Control design with a non-ideal excitation and parametric uncertainties - Goncalves Vicente, Joselma Pinheiro [UNESP]; Chavarette, Fabio Roberto [UNESP]; Pereira Roefero, Luiz Gustavo [UNESP] (Scipedia S L, 2019)
In this work, a non-ideal system based on the Mathieu-Van der Pol System is modeled considering its parameters as uncertain, which makes it closer to reality. Numerical simulations are presented demonstrating that the system has a chaotic behavior with three positive Lyapunov exponents. Given such unstable and unpredictable behavior, the linear optimal control design is proposed to reduce the chaotic movement of this system to a fixed point. The simulation results show that the identification by Linear Optimal Control is very effective.
Keywords: Non-Ideal System; Uncertain Parameters; Optimal Linear Control